Analisis Pendapatan Usaha Tani Tanaman Pangan Lahan Basah di Desa Aimoli - Narita Yuri A.; Daud H. Bang; Jeni M. Loban (Jurnal Ilmiah Wahana Pendidikan, 2023)
Communities in rural areas characterized by agriculture as an economic basis, especially in Aimoli Village, are people whose livelihoods are mostly in agriculture. Therefore, with agricultural business, these people can meet their needs. In this study, the authors conducted actual research on what factors influenced the income of wetland food crop farming in Aimoli Village. As for what is used in analyzing is by using multiple regression analysis. And the factors that are assumed to affect the income of the farming business are capital, land area, and fertilizer used in rice cultivation. The results obtained from this study are that the three factors, namely capital, land area, and fertilizer used in rice cultivation, have an effect on farming income